Numerical Study of a Waste Heat Recovery Thermogenerator System - Henriquez-Vargas, L; Donoso-Garcia, P (Springer Verlag, 2019)
This paper presents a numerical study on waste heat recovery from a fluid stream using thermoelectric elements for energy harvesting. Two fluids were tested, air and steam, and the voltage and overall efficiency were computed for different sets of operational conditions. The mathematical description considered turbulent regime and coupled transport phenomena for the description of the main thermoelectric effects. Numerical solution was achieved using ANSYS/FLUENT commercial software with complementary implementations of user-defined scalars and user-defined functions to account for the mathematical model specific needs. The system global efficiency was computed for a pair of heat extraction conditions and different operational variables giving values within [0.11–9.22] (%). It was found that the global efficiency increases with the fluid temperature and the decrease in the external thermal resistance. For all cases studied, the global efficiency was greater when air was used as a heat carrier fluid due to its specific heat values which were about half the steam ones. © 2019, The Brazilian Society of Mechanical Sciences and Engineering.